STUDY ON EFFECT OF SALINITY TO ASSIMILATION CAPACITY OF ORGANIC POLLUTANTS IN THE CU DE RIVER’S WATER - Tu, Nguyen Thi Thanh; Si, Phung Chi; Thang, Dinh Xuan (Vietnam Journal of Marine Science and Technology, 2014)
This article presents the research results on effect of salinity to assimilation capacity of organic pollutants in the Cu De river’s water. It is one of the most important issues for studying the carrying capacity of biodegradable organic pollutants on the river basin. The results of three monitoring periods shown that the salinity (S-‰) is decreasing from estuary to upstream (from cross section MC1 to cross section  MC5), fluctuating within 2,73 ÷ 22,27‰, meanwhile assimilation capacity of organic pollutants is increasing. The linear correlation between salinity and disintegrated organic pollutants (∆BODt) is presented  by the equation: Y(∆BODmh)= 10,72 – 1,166*S